Reduction of loading time in a drywall industry: application of Lean Manufacturing tools - Araujo, Andressa Clara Barbosa de; Porto, Yuri Boaventura Santana; Couto, Pedro Henrique Oliveira; Silva, Fabyane Dias da; Pimentel, Cristiane Agra (Brazilian Journal of Production Engineering, 2025)
This study investigates the application of Lean Manufacturing tools in the shipping sector of a Drywall industry, aiming to optimize loading time and operational efficiency. Through a case study, conducted through direct observation and data collection, significant improvements in organization and productivity were identified. Quantitative results demonstrate an 11.75% reduction in loading time and route optimization. Qualitatively, the implementation of visual management and process standardization provided greater clarity and organization in the work environment, resulting in increased operator engagement. Despite initial resistance, the study validates the effectiveness of Lean practices in civil construction, offering a replicable model to improve logistical and organizational processes.